Fusarium infection and mycotoxin contamination in preharvest and stored maize in Benin, West Africa - Marasas, Walter F.O. (Walter Friedrich Otto) (University of Pretoria, 2013)
Thesis (PhD (Microbiology))--University of Pretoria, 2004.